Are environmental sustainability and happiness the keys to prosperity in Asian nations?. (December 2020) - Kaklauskas, A.; Dias, W.P.S.; Binkyte-Veliene, A.; Abraham, A.; Ubarte, I.; Randil, O.P.C.; Siriwardana, C.S.A.; Lill, I.; Milevicius, V.; Podviezko, A.; Puust, R.
Highlights: Six compiled multiple regression models of success and happiness in Asian nations range over a 25-year period. The environment, success and happiness (ESH) of Asian nations correlates with the macro-level environment. INVAR method delivers numerical guidelines for reforming an ESH. Countries with superior well-being, values-base, human development and other macro indicators scored best in ESH. The analysis in this multicriteria study covers the ESH trends in Asian nations. Abstract: Various research prove that happy nations are prosperous in numerous areas containing GDP, productivity, social support and inclusion, health, lower corruption and environmental sustainability. The analysis in this multicriteria study covers the environmental sustainability, success and happiness trends in Asian nations during a 25-year time span. Strong and average correlations amongst the success, happiness and environmental sustainability, of Asian nations, in one regard, and, in another regard, the macroeconomics, well-being and human development, values-based, quality of life and environmental indicators were established across numerous statistical databases. Six multiple regression models of success and happiness in Asian nations were compiled with the assistance of IBM SPSS Statistics. The linear regression model of success in 40 Asian nations illustrates how nine independent variables explain 90.7 percent of the significances of results. The 19-Asian nation, multiple regression happiness model show how 16 independent variables account for 99.5% of the Happiness index weight dispersion.